Banking sector liberalization and economic growth: case study of Pakistan - Saqib, Najia (Journal of Business Economics and Management, 2016)
Economic theory suggests that sound and efficient financial systems channel capitals to its most productive uses are beneficial for economic growth. Sound and efficient financial systems are especially important for sustaining growth in developing countries. This paper examines the impact of banking sector liberalization on long-term economic growth in Pakistan by using a time series data for the period 1971–2011. The results show that there exist a significant positive long run relationship between banking sector development and economic growth in the country. The sensitivity analysis also shows that the relationship remain positive and significant no matter what combination of the omitted variables are used in the basic model. Thus, our findings support the core idea that banking sector development stimulates long term economic growth in a country.